Driving responsible research and innovation: Science, society and the energy movement - Malan, N.; Simpson, Z.; Janse van Rensburg, N. (South African Journal of Higher Education, 2017)
South Africa faces the challenges of poverty, unemployment and inequality, as well as looming problems regarding water, energy and food. Science, technology and engineering are able to address some of these challenges but are often inaccessible and unfamiliar to the general public. Research and innovation in these fields needs to be increased, and undertaken in partnership with multidisciplinary stakeholders. This article uses the example of an engineering education initiative, the African Solar Drive, to illustrate how this may be achieved. It discusses recent developments in the philosophy of science that have emphasised responsibility in research and development, the similarities of these with action research methodologies and the relevance of these for the concerns South Africa faces at the moment. It presents a general methodology for science-society engagement and locates the African Solar Drive as a prelude to such engagement between higher education and the general public.